Non-linearities in Real Interest Rate Parity: Evidence from OECD and Asian Developing Economies - Ahmad Zubaidi, Baharumshah; Liew, Venus Khim-Sen; Mittelhammer, Ron (Taylor & Francis, 2010)
This paper investigates the validity real interest rate parity (RIP) for a sample of 19 OECD and Asian developing economies. The distinction of this paper is that we exploit both linearity and non-linear unit root tests as advocated by Dufrénot et al. (Applied Economics, 38, pp. 203–229, 2006) to validate the parity. The major finding are: (i) the alignments from real interest rate differentials (RIDs) are corrected in a non-linear fashion and that the adjustments is asymmetric in both size and speed; (ii) that RIP holds for the developed and developing countries; and (iii) the empirical results are invariant with respect to the US, Japan or Germany as the centre country.